General election 14, contentious journalism, and the collapse of the national front / Mohd Amirul Akhbar Mohd Zulkifli - Mohd Zulkifli, Mohd Amirul Akhbar
The Malaysian political landscape has recorded its "tectonic" shift with the collapse of the National Front after nearly 60 years leading the country. The National Front has not only suffered its worst defeat in GE14, but its fall is also marred as a watershed in modern politics of this country. This study analyzed the development of political issues in Malaysia after GE13 towards GE14. A qualitative research method was conducted using historical study and content analysis based on secondary data resources, which involved books, journals, research papers and newspapers. Through the process it developed an understanding towards the issues debated in GE13 and GE14, supported by the dynamism of contentious journalism with shared information via the social media platforms. In essence, from analysis of this study, there is evident relationship between contentious journalism and its contribution towards the fracture of hegemony of the National Front towards Pakatan Harapan.